2022
DOI: 10.1111/jcmm.17439
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D1 promotes cervical cancer progression by activating the RAS pathway

Abstract: This study aimed to further investigate the effect of PLD1 on the biological characteristics of human cervical cancer (CC) cell line, CASKI and the potential related molecular mechanism. CRISPR/Cas9 genome editing technology was used to knock out the PLD1 gene in CASKI cells. Cell function assays were performed to evaluate the effect of PLD1 on the biological function of CASKI cells in vivo and in vitro. A PLD1‐overexpression rescue experiment in these knockout cells was performed to further confirm its functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The Ras pathway is linked to the growth of cervical cancer. Previous studies have shown that PDL1 promotes cervical cancer development by activating RAS pathway, while DUSP7 prevents cervical cancer progression by inactivating RAS pathway 55,56 . Previous studies have found that stimulation of MAPK signal transduction pathway can promote the proliferation and metastasis of cervical cancer cells 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ras pathway is linked to the growth of cervical cancer. Previous studies have shown that PDL1 promotes cervical cancer development by activating RAS pathway, while DUSP7 prevents cervical cancer progression by inactivating RAS pathway 55,56 . Previous studies have found that stimulation of MAPK signal transduction pathway can promote the proliferation and metastasis of cervical cancer cells 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PDL1 promotes cervical cancer development by activating RAS pathway, while DUSP7 prevents cervical cancer progression by inactivating RAS pathway. 55 , 56 Previous studies have found that stimulation of MAPK signal transduction pathway can promote the proliferation and metastasis of cervical cancer cells. 57 The nuclear factor b (NF‐kB) family of transcription factors controls inflammation and immune responses in intricate and important ways.…”
Section: Discussionmentioning
confidence: 99%